Comments on the Canada Media Fund's English Regional Production Policies by the English-language Arts Network of Quebec - English Language Arts Network (ELAN) (2009)
The Canadian Television Fund (CTF) has made the English-language regions synonymous with the official-language minority in Quebec. While regional policies overlap with official-language policies in many ways, they are each distinct and need to be addressed differently. The Official Languages Act gives the English-language minority in Quebec the same status as the French-language minority outside Quebec. However, the CTF has not recognized that the official-language minority community (OLMC) in Quebec has the same rights and legal status as the French-language minority outside Quebec. Thus, Montreal production is not given regional status for the BPE, nor is there a Quebec OLMC production fund similar to the production fund (FLPOQ) available to the French-language minority outside Quebec.
Keywords: Official Language Minority Community (OLMC)

Re: Support of the Canadian Broadcasting Corporation (CBC) - Rodgers, Guy (2009)
Keywords: Official Language Minority Community (OLMC)